Hydric conflict and territorial defense: Women in the Peasant Movement of Santiago del Estero, Argentina - Mariela Pena (Íconos)
Latin America is currently undergoing, to a worrying degree, the advance of the extractive-export model, which aggravates distributive conflicts associated with territorial and water resources. In the face of these processes, environmental resistances have been articulated by vulnerable peasant-indigenous populations, who oppose this productivist paradigm by advancing sustainable development ethics. This study is based on the ethnographic case of Santiago del Estero, a province in the center-north of Argentina, traditionally considered “unproductive”, which has been drastically affected by agriculturization. There, the populations affected by land grabbing, evictions, and environmental contamination have formed the Peasant Movement of Santiago del Estero (Mo.Ca.Se). From a gender perspective and an anthropological approach focused on observation and interviews, we explore the impact of environmental injustices – specifically, water injustice – on peasant-indigenous communities and the extreme vulnerability that it entails for women and girls. It is concluded that women play a transcendental role in the resilience strategies of their communities, within a context of scarcity, violence, and dispossession. At the same time, another of the findings is that collectively organized territorial defense facilitates their access to water and other resources, through the generation of broader networks and alliances, even on a transnational scale.